Regionale Wasserstoffpotenziale; Regional hydrogen potentials - Michael Bräuninger; Silvia Stiller; Mark-Oliver Teuber (Wirtschaftsdienst, 2022)
– The paper analyses the potential of the hydrogen economy in German districts and cities. The paper focuses particularly on regions suffering from strong ongoing structural change. The assessment is based on quantitative indicators for the supply structures (renewable energy, pipeline network), the demand side (industry, transport and heat), and on regional knowledge (research institutions and projects). The results show four regional clusters suffering from structural change that could potentially establish a hydrogen economy. These regions will benefit from investments in hydrogen structures and the associated strengthening of regional value chains.
Keywords: R11; R12; Q42; 330; Wasserstofftechnik; Deutschland